Hydrography at Master and IHO Cat-A Level At Ensta-Bertagne - Seube, N.; Debese, N.; Moitie, R. (The International Hydrographic Review, 2011)
This paper aims at analyzing the requirements for the education of surveyors acting at the IHO Cat A level, namely those who will manage independently hydrographic fieldworks. We also propose an analysis of the educational capacity in hydrography, with regards to both the professional demand of hydrographers and the required level in the industry. This paper is the fruit of a work conducted for four years at the ENSTA-Bretagne, the French IHO Cat A course. We use the results of a complete redesign of our course that occurred in 2006 and from our three years of feedback from the industry.